IMPROVING WRITING ABILITY THROUGH OUR FIVE SENSES - Ubaydullaeva, Gulkhayo (Educational Research in Universal Sciences, 2022)
Nowadays English language has become a dominant language on communication among different nations in all areas. People try to find proficient and facile way both in teaching and studying the English language. This article deals with the issues on methodology in teaching writing comprehension through learners of English as a second language. With the help of this work we will be aware of one more way in enhancing writing skills. The five senses technique suit for all pupils inspite of their age and ability.